2023
DOI: 10.3389/fcell.2023.981425
|View full text |Cite
|
Sign up to set email alerts
|

HURP localization in metaphase is the result of a multi-step process requiring its phosphorylation at Ser627 residue

Stylianos Didaskalou,
Christos Efstathiou,
Sotirios Galtsidis
et al.

Abstract: Faithful chromosome segregation during cell division requires accurate mitotic spindle formation. As mitosis occurs rapidly within the cell cycle, the proteins involved in mitotic spindle assembly undergo rapid changes, including their interactions with other proteins. The proper localization of the HURP protein on the kinetochore fibers, in close proximity to chromosomes, is crucial for ensuring accurate congression and segregation of chromosomes. In this study, we employ photoactivation and FRAP experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In comparison, the 285-400 segment of HURP markedly reduces Kif18A’s velocity, which may be due to an interaction between this region and the 1-480 segment of Kif18A. Interestingly, a cross-talk between the N and C-termini of HURP has been described in previous studies, showing that HURP phosphorylation in the C-terminus by the Aurora A kinase can regulate accessibility of its N-terminus and contribute to HURP localization 29,41,42 . Therefore, the C-terminus of HURP may also regulate the activating role of the HURP N-terminus, resulting in fewer and slower Kif18A runs on the microtubule.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In comparison, the 285-400 segment of HURP markedly reduces Kif18A’s velocity, which may be due to an interaction between this region and the 1-480 segment of Kif18A. Interestingly, a cross-talk between the N and C-termini of HURP has been described in previous studies, showing that HURP phosphorylation in the C-terminus by the Aurora A kinase can regulate accessibility of its N-terminus and contribute to HURP localization 29,41,42 . Therefore, the C-terminus of HURP may also regulate the activating role of the HURP N-terminus, resulting in fewer and slower Kif18A runs on the microtubule.…”
Section: Discussionmentioning
confidence: 86%
“…HURP-mediated activation could promote the enrichment of Kif18A in chromatin-proximal regions of the K-fibers, where HURP localizes during metaphase forming a comet-like gradient 15,42 . Yet, due to saturation of the binding sites by HURP, we observed that increased recruitment of motors to microtubules does not lead to productive motility at higher HURP concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from RanGTP, other studies have determined that the function of human HURP is also positively regulated by Aurora A phosphorylation. Phosphorylation of the C-terminus of human HURP is necessary for localization to spindle MTs 29,52 . Furthermore, this phosphorylation is hypothesized to contribute to its dynamic localization to the MTs near chromosomes during metaphase 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in acentrosomal systems, such as Drosophila oocytes, mouse oocytes, and Xenopus egg extract, loss of HURP leads to spindle assembly defects and a reduction of spindle MT density 17,[26][27][28] . Additionally, HURP directly or indirectly interacts with TPX2 and augmin subunits in various species [28][29][30] , which prompted us to investigate HURP's role in branching microtubule nucleation.…”
Section: Introductionmentioning
confidence: 99%